Entrepreneurial Leadership and Entrepreneurial Performance in Start-Ups: A Moderated Serial Mediation Model - Pu, Bo; Ji, Siyu; Sang, Wenyuan; Tang, Zhiwei (Frontiers in Psychology, 2022)
The purpose of this study is to explore the impact of entrepreneurial leadership on entrepreneurial performance in start-ups. Specifically, a moderated serial mediation model was developed to investigate the mediating role of tacit knowledge sharing and job embeddedness and the moderating effect of career growth opportunities. Data was collected from 376 start-up employees via an online survey platform. Using hierarchical multiple regression and Hayes’ PROCESS Macro by SPSS 21.0, and structural equation modelling by AMOS 23.0, support was found for both mediation and moderation effects. Results showed that entrepreneurial leadership significantly positively affects entrepreneurial performance by mediating with tacit knowledge sharing and job embeddedness. Moreover, career growth opportunities moderate the serial mediating effect of tacit knowledge sharing and job embeddedness between entrepreneurial leadership and entrepreneurial performance. This study provides theoretical guidance for entrepreneurial leadership to improve entrepreneurial performance.